DEVELOPING WRITING MATERIALS IN RECOUNT TEXT FOR THE EIGHT GRADE STUDENTS AT SMP RK SERDANG MURNI LUBUK PAKAM - Sri Agus Turnip; Yeni Erlita; Maya Octora (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
The objectives of this study was to develop the writing materials in recount text for the eight grade students at SMP RK Serdang Murni Lubuk Pakam. This was a Research and Development (R&D) study. The subjects of the study were the students of eighth grade of SMP RK Serdang Murni Lubuk Pakam. The research procedures, were adapted from Jolly and Bolitho’s model in Tomlinson (1998) with some modifications, consisting of conducting the need analysis, writing the course grid, developing the first draft, getting expert judgment and evaluating the first draft, also revising the first draft of the materials.The instruments to collect the data were need analysis questionnaire and expert judgment questionnaire. The data from the need analysis were analyzed quantitatively using frequency and precentage, then the results were used to develop the course grid. The data from the expert judgment were analyzed quantitatively through descriptive statistics while the suggestions were used to revise the first draft of the materials. The product of this study is a set of writing materials of recount text entitled “Guide for Writing” for students of eighth grade of SMP RK Serdang Murni Lubuk Pakam. The writing material is “My Unforgettable Experience”. It  consists of Pre-writing, Drafting, Responding, and Editing tasks ranging 15 tasks. Based on the research findings from the expert judgment, the whole aspects of the developed materials were 3.76 which was in the range of 3.25 < x ≤ 4 and can be categorized as “very good”. Keywords: Recount Text, Writing Materials, R&D Method